Symbolic negotiation and resignification of Banten’s Debus Art as cultural mediation between local tradition and the digital era - Azizah, Fathiyyah (Universitas Muhammadiyah Malang, 2026)
This study examines the symbolic meaning of Debus, a traditional martial art performance from Banten, as a representation of local cultural identity in the modern era. Debus is understood not only as an extreme physical performance, but as a form of cultural communication that embodies spiritual symbols, social values, and philosophical worldviews of the Banten’s community. Employing a qualitative descriptive approach grounded in cultural communication and semiotic perspectives, this research analyzes ritual practices, bodily expressions, and historical narratives as symbolic media of meaning. Data were collected through in-depth interviews with senior practitioners (jawara), ritual masters (pawang), and younger audience members. Fieldwork was conducted over approximately three months across multiple Debus performance and transmission sites in Banten Province. The findings reveal three main functions of Debus. It acts as a symbol of cultural resilience, especially emphasized by elder practitioners in response to socio-political marginalization. In addition, Debus functions as a mechanism for constructing communal identity, shaped by tensions between maintaining ritual authenticity and adapting to tourism and digital media. These results challenge common assumptions that position traditional performance as either static heritage or fully commodified spectacle. The study suggests that symbolic communication in contemporary society is increasingly fluid and influenced by mediation, where cultural resilience involves not only preservation but also reinterpretation and transformation. This study contributes to cultural communication scholarship by emphasizing the enduring relevance of traditional arts as symbolic communication systems in modern societies and offers practical implications for cultural preservation through education and sustainable cultural policy. Penelitian ini menggunakan makna simbolis seni Debus khas Banten sebagai representasi identitas budaya lokal di era modern. Debus dipahami tidak hanya sebagai pertunjukan fisik yang ekstrem, tetapi sebagai bentuk komunikasi budaya yang mengandung simbol-simbol spiritual, nilai-nilai sosial, dan pandangan hidup masyarakat Banten. Dengan menggunakan pendekatan deskriptif kualitatif yang berlandaskan perspektif komunikasi budaya dan semiotika, penelitian ini menganalisis praktik ritual, ekspresi tubuh, serta narasi historis sebagai media simbolik pembentuk makna. Data dikumpulkan melalui wawancara mendalam dengan praktisi senior (jawara), pawang (master ritual), dan anggota audiens muda. Penelitian lapangan dilakukan selama kurang lebih tiga bulan di berbagai lokasi pertunjukan dan transmisi Debus di Provinsi Banten. Temuan penelitian mengungkap tiga fungsi utama Debus. Debus berfungsi sebagai simbol ketahanan budaya, yang terutama ditekankan oleh praktisi senior dalam merespons marginalisasi sosial-politik. Selain itu, Debus berfungsi sebagai mekanisme pembentukan identitas komunal yang dipengaruhi oleh ketegangan antara menjaga keaslian ritual dan menyesuaikan diri dengan tuntutan pariwisata serta media digital. Temuan ini menantang asumsi umum yang memposisikan pertunjukan tradisional sebagai warisan statis atau sekadar tontonan yang terkomodifikasi sepenuhnya. Penelitian ini menunjukkan bahwa komunikasi simbolik dalam masyarakat kontemporer semakin bersifat cair dan dipengaruhi oleh mediasi, sehingga ketahanan budaya tidak hanya mencakup pelestarian, tetapi juga reinterpretasi dan transformasi. Penelitian ini berkontribusi pada kajian komunikasi budaya dengan menegaskan relevansi berkelanjutan seni tradisional sebagai sistem komunikasi simbolik dalam masyarakat modern, serta memberikan implikasi praktis bagi pelestarian budaya melalui pendidikan dan kebijakan budaya yang berkelanjutan.